Pengaruh Parasocial Relationship dan Electronic Word of Mouth (E-WOM) di Instagram terhadap Purchase Intention Produk Adidas Samba (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Pancasila) - Wardany, Melani Eka; Wulandjani, Harimurti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the influence of parasocial relationships and electronic word of mouth (E-WOM) on Instagram on the purchase intention of Adidas Samba products among students of the Faculty of Economics and Business, Pancasila University. The sampling method used was non-probability sampling with a purposive sampling technique, with a sample size of 100 respondents. The data collection instrument used a questionnaire distributed through Google Form. This study uses a quantitative approach with SPSS version 29 analysis techniques and uses validity tests, reliability tests, classical assumption tests, multiple linear regression tests, as well as t-tests and F-tests. The results show that parasocial relationships and E-WOM partially and simultaneously have a positive and significant effect on the purchase intention of Adidas Samba products. This finding indicates that the stronger the emotional closeness with influencers and the more positive reviews consumers receive on Instagram, the higher the students' purchase interest in Adidas Samba products.